Evaluación del potencial energético del aceite de piñón en el motor ISUZU serie DMAX como fuente alternativa de energía en la ciudad de Latacunga. Utilización como biocombustible en motores diesel en proporción para reducir la polución. - Erazo Laverde, Washington Germán (2013)
This investigation determined the energy potential available to the oil pinion as a source of alternative energy fuel in diesel engines Isuzu series DMax in the city of Latacunga, through a work of experimental field using measuring equipment technology has relevant information generated for the purpose of developing a proposal for use in proportions of 5, 10, 15 and 20 percent in combination with diesel to reduce pollution produced by diesel vehicles and turning it into an energy alternative Laboratory tests refer to measurements of temperature variation versus time for the energy potential of biofuel in the above percentages and pure for use in the Isuzu DMax diesel engine series, to verify their influence on torque, power, opacity, fuel consumption and overall engine performance. The research literature studied in texts, articles indexed, digital documents, secondary sources focused to apply a consistent methodology to the academic degree of Master in Energy Management. Measurements are essential and fundamental research, and allowed to evidence the energy potential available to the gear oil as an alternative energy source, characterizing their use to reduce pollution in the city of Latacunga